Holland flowering : how the Dutch flower industry conquered the world - Gebhardt, Andrew (Amsterdam : Amsterdam University Press, 2014)
Growing tulip bulbs on the moon, and a tulip shaped island in the North Sea. Frederick Ruysch's wunderkammer and contemporary bloemencorsos. A Dutch-Chinese billionaire, aka the Orchid King, recreates a 'Dutch' town in northeast China complete with a replica of Amsterdam's central station and the International Court of Justice. A retired grower recalls a life in flowers, from the Second World War to the European Union. Dutch development policies in Ethiopia today and its former civilizing mission in Java. Auctions, cooperatives, networking, commodity culture, Dutch masculinity, and globalization. These are some of the imaginaries, themes, curious details, and perspectives you will encounter in this book. All of them pivot around Dutch flower culture today and in the Dutch Golden Age, and directly or indirectly link to Aalsmeer's flower auction, the world's largest, located not far from Amsterdam.
Title from publisher's bibliographic system (viewed on 01 Jan 2021).
Keywords: Cut flower industry -- Netherlands -- History